Juridical Review of Default in The Sale and Purchase Agreement Letter Land - Tegar (UM Purwokerto Press, 2023)
This research was conducted on the court decision Number: 12 / Pdt.G / 2023 / PN Clp) regarding the dispute over the sale and purchase agreement of land rights with the aim of analyzing the validity of the sale and purchase agreement and analyzing the default committed by the seller (Defendant).This research uses a normative juridical approach method with prescriptive research specifications. The types and sources of legal materials contained in this research come from secondary data which includes primary, secondary, and tertiary legal materials using the literature study data collection method. Based on the results of the research conducted, it is found that the sale and purchase agreement of land rights between the debtor and the creditor that was not carried out in front of a Land Deed Official (PPAT) in this case is valid based on the results of the review according to Customary Law, the Civil Code and Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles (UUPA) which includes Government Regulation Number 24 of 1997 concerning Land Registration. However, because the sale and purchase was not carried out before a PPAT, the sale and purchase agreement basically only applies to the parties, so that the transfer of rights can be requested to be proven in court. The Panel of Judges in considering and deciding that the debtor made a default was considered appropriate and appropriate, because the wrong elements were found which included negligence of the debtor's actions and the debtor's actions included a form of non-achievement at all because the Seller did not carry out his obligation to take care of the process of baliknama at the Notary / PPAT office as well as to make a deed of sale and purchase.